As Artes Visuais nas práticas das professoras de uma Unidade Municipal de Educação Infantil de Belo Horizonte - Marcia Darquia Nogueira da Silva (2015)
This dissertation analyzes conceptions and practices in Visual Arts held by teachers in a Municipal Early Education Unit - UMEI in the city of Belo Horizonte, MG. Visual Arts practices were analyzed based on conceptions, perceptions and evaluations revealed by teachers in relation to the proposals carried out in daily routine at the institution. The contextualization of Early Education field and the analysis of the theoretical debate regarding the relation between Visual Arts and education contributed to conceptualization of Early Education as childs right and the first stage of basic education; and to define Visual Arts as a fundamental component of the curriculum, to be included in institutions educational proposals. As methodology to understand the role of Visual Arts in early education, we reviewed literature about both fields and analyzed official national and municipal documents ruling early education. In order to understand teachers practices, participant observation in daily UMEI routines and carried out semi-structured interviews with seven women and one man, teaching at the institution. As a result of our research, three conceptions of Visual Arts were found among the teachers: Visual Arts as free expression of feelings; Visual Arts as human capacity to represent and symbolize, associated with visual images, artists and their works; and Visual Arts as a support and tool for other school activities. Furthermore, we observed that there is a kind of distance between conceptions and practices. In the interviews, the conception of Visual Arts as a support and tool for other activities was less mentioned, although in teachers practices, it is always linked to another educational goal. However, in monitoring everyday actions it was found that the teachers from the referred institution strive to study, research and delve into the sense and meaning of the Visual Arts in Early Education.